2019
DOI: 10.1111/os.12547
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Comparison of Liposomal Bupivacaine with Femoral Nerve Block for Pain Control Following Total Knee Arthroplasty: An Updated Systematic Review and Meta‐Analysis

Abstract: To compare the efficacy of liposomal bupivacaine (LB) and femoral nerve block following total knee arthroplasty, we conducted this systematic review and meta-analysis. 11 trials with 2,908 patients were included in this study. The pooled data demonstrated that total morphine consumption equivalents during the hospital stay was significantly increased in FNB group. In addition, LB has significantly better outcome in view of the postoperative functional recovery, such as the odds of fall, the incidences of strai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
7
0
1
Order By: Relevance
“…Another meta-analysis 191 found that the use of continuous peripheral nerve blocks (FNB or ACB) does not provide superior analgesic benefit over single shot LIA. The potential benefits of using liposomal bupivacaine has been evaluated in six meta-analyses 125,[192][193][194][195][196][197] and a Cochrane review. 198 The role of liposomal bupivacaine in LIA for TKA remains unclear because of conflicting evidence.…”
Section: Local Infiltration Analgesiamentioning
confidence: 99%
“…Another meta-analysis 191 found that the use of continuous peripheral nerve blocks (FNB or ACB) does not provide superior analgesic benefit over single shot LIA. The potential benefits of using liposomal bupivacaine has been evaluated in six meta-analyses 125,[192][193][194][195][196][197] and a Cochrane review. 198 The role of liposomal bupivacaine in LIA for TKA remains unclear because of conflicting evidence.…”
Section: Local Infiltration Analgesiamentioning
confidence: 99%
“… 114 Similarly, a recent meta-analysis showed that periarticular injection with liposomal bupivacaine is associated with faster functional recovery but no difference in pain scores was seen when compared with FNB. 115 However, another meta-analysis compared liposomal bupivacaine in periarticular injections for TKA with traditional LAs and found no clinical difference in pain reduction neither opioid consumption 116 . Although, the authors acknowledge the lack of studies with comparable procedures, which may limit their conclusions.…”
Section: Long-acting Anestheticsmentioning
confidence: 99%
“…Total knee arthroplasty (TKA) is 1 of the most effective methods for end-stage of knee osteoarthritis (OA) and improve the quality of life of patients. [ 1 , 2 ] According to epidemiological statistics of OA, the incidence of OA in people over 65 years and over 80 years old can reach 50% and 80% respectively. [ 3 ] Over 90 000 TKAs are performed annually in England and Wales.…”
Section: Introductionmentioning
confidence: 99%